A convenient method for the synthesis of α-carboxylate ester bromolactones via bromolactonization of alkenoic diesters. Issue 12 (2nd March 2016) - Wong, Ying-Chieh; Yeung, Ying-Yeung
Abstract : A simple and efficient synthesis of α-ester bromolactones has been developed through the electrophilic bromocyclization of olefinic 1, 3-diesters. Abstract : We developed a simple and efficient method to construct a variety of α-ester bromolactones in good to excellent yields with high diastereoselectivies. The protocol uses readily prepared malonate ester derivatives as substrates, water as an additive and inexpensive N -bromosuccinimide as the halogen source; no catalyst or toxic additive is required. The resulting substituted bromolactones are the fundamental units of many useful molecules.